PELAKSANAAN PENGAMANAN OLEHPETUGASPEMASYARAKATAN TERHADAP WARGA BINAAN DI RUMAH TAHANAN NEGERI KELAS II B RENGAT BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PERMASYARAKATAN - Ayu, Ade Fitri; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Correctional officers who carry out the task of fostering and securing prisoners in Law No. 12 of 1995 on the Acting Functional Correctional Law Enforcement. Functional correctional officers are law enforcement officers who carry out tasks in the field of coaching, mentoring, and security of inmates. Still away from the law enforcement, as expected due to the persistence of the constraints and challenges in matter of law, the legal apparatus, facilities and infrastructure as well as other factors that influence it. Although the legal development takes time, but the need for the law to shelter may not be delayed even prove to the demands of society is increasingly rising, and should be recognized also there are the excesses in the application and enforcement. The purpose of this thesis, namely; First, to investigate the implementation of safeguards by correctional officers against inmates in detention State Class II B Rengat according to Law No. 12 of 1995 concerning Corrections, second, to determine obstacles correctional officers in the implementation of safeguards against prisoners in a detention Class II B Rengat according to Law No. 12 of 1995 concerning Corrections, Third, To know the efforts made in the implementation of security correctional officers against inmates home state custody Class II B Rengat according to Law No. 12 of 1995 concerning Corrections.Keywords: Security-State Prison Inmates